Application of Levin’s transformations to virial series - Florindo, C.C.F.; Bassi, A.B.M.S. (Condensed Matter Physics, 2014)
A new method to estimate high-order virial coefficients for fluids composed of equal three-dimensional rigid spheres is proposed. The predicted B₁₁ and B₁₂ values are in good agreement with reliable estimates previously reported. Not only, a new application of the Levin's transformations is developed, but a new way of using Levin's transformations is suggested. For the virial series of packing factor powers, this method estimates the B₁₃ value near 173.